2015
DOI: 10.1039/c4ta05643d
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical graphene oxide/polyaniline nanocomposites prepared by interfacial electrochemical polymerization for flexible solid-state supercapacitors

Abstract: Hierarchical graphene oxide/polyaniline (GO/PANI) nanocomposites deposited on flexible substrates were synthesized by one-step interfacial electrochemical polymerization. PANI nanorods were coated on the surface of GO to form a three-dimensional nanostructure, which was prepared by the polymerization at the water/chloroform interface. The current density for interfacial electrochemical polymerization was up to 0.5 mA cm À2 , which is one-fold higher than that used in conventional electrochemical methods for na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(44 citation statements)
references
References 63 publications
(90 reference statements)
0
43
0
1
Order By: Relevance
“…[53,54] The high intensity of the C-N +• stretching vibration at 1337 cm -1 suggested that PANi in the composites was in the doped state. [55] Raman footprints of PEDOT:PSS (i.e. stretching deformation of Cβ-Cβ at 1372 cm -1 , Cα-Cα inter-ring stretching vibration at 1256 cm -1 , and oxyethylene ring deformations at 577 and 994 cm -1 ) [56] were all present in the GO/PA-PE composites.…”
Section: Printable Inks and Extrusion Printing Processmentioning
confidence: 94%
“…[53,54] The high intensity of the C-N +• stretching vibration at 1337 cm -1 suggested that PANi in the composites was in the doped state. [55] Raman footprints of PEDOT:PSS (i.e. stretching deformation of Cβ-Cβ at 1372 cm -1 , Cα-Cα inter-ring stretching vibration at 1256 cm -1 , and oxyethylene ring deformations at 577 and 994 cm -1 ) [56] were all present in the GO/PA-PE composites.…”
Section: Printable Inks and Extrusion Printing Processmentioning
confidence: 94%
“…Synthesis of conductive polymers can also be performed at the three phase junction systems [166][167][168][169][170][171][172].…”
Section: Organic Polymersmentioning
confidence: 99%
“…PANI itself possesses a very high theoretical specific pseudo‐capacitance of 2000 F g −1 and unique fast redox and acid–base doping/dedoping properties. High‐performance supercapacitors based on graphene/PANI nanocomposites have been well‐studied by many groups …”
Section: Graphene/polymer Nanocomposites For Supercapacitorsmentioning
confidence: 99%